As you sow, so shall you reap: Assessing drivers of socially responsible investment attitude and intention - Aashish Garg (17380339) (2022)
Socially responsible investment (SRI) is a form of investment that strives to generate both social and financial rewards for investors. This research seeks to examine the Indian retail investors' investment behaviour towards SRI. The growth is being observed in the number of retail investors looking to invest in firms that promote social or environmental goals and act ethically. For this purpose, the data were obtained from 433 participants through an online survey. The research hypotheses were tested using covariance-based structural equation modelling (SEM). The findings suggest that investors' values (collectivism and biospheric values), biases (social responsibility bias and reliance on expert bias), and perceived performance of SRI contribute positively to the intentions towards SRI. Also, the results highlight that attitude mediated all hypothesised relationships except for the relationship between collectivism and intention and reliance on expert bias and intention towards SRI. This research also established that investors with high social self-efficacy tend to have high intentions towards SRI. The significant implications for theory and practice have been discussed. Other Information Published in: Technological Forecasting and Social Change License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.techfore.2022.122030